Download presentation

Presentation is loading. Please wait.

Published byElla Fagan Modified over 2 years ago

1
Substitution

2
Take OUT the variable and PUT in the new expression y = 4x + 1 2x – y = 9 y = 4x + 1 2x – y = 9 -2x – 3 = 6x + 1 y = -2x -3 y = 6x + 1 y = -2x - 3 y = 6x +1 2x – (4x + 1) = 9

3
Take OUT the variable and PUT in the new expression y = 4x + 1 2x – 2y = 9 y = 4x + 1 2x – 2y = 9 y = 6(-2x – 3) + 1 x = -2x -3 y = 6x + 1 x= -2x - 3 y= 6x +1 2x – 2(4x + 1) = 9

4
Your Turn! Write the NEW equation after you substitute.

5
-2x – 3(6x-11) = -7 y = 6x – 11 -2x – 3y = -7

6
2x – 3(x-1) = -1 2x – 3y =-1 y = x - 1

7
5x – 4(-3x + 5) = -3 y = -3x +5 5x – 4y = -3

8
(-5x-17) = -x – 1 or (-x – 1) = -5x - 17 y = -x -1 Y = -5x - 17

9
4x – 3(-2) = 18 y = -2 4x – 3y = 18

10
-7(-2y + 11) – 2y = -13 x= -2y x – 2y = -13

11
(-5x - 21) = 4x + 6 or (4x + 6) = -5x - 21 y = -5x – 21 y = 4x +6

12
-5x + (1/2x-2) = -2 y = 1/2x – 2 -5x + y = -2

13
-3(-3y + 1) – 3y = -15 x = -3y x – 3y = -15

Similar presentations

© 2016 SlidePlayer.com Inc.

All rights reserved.

Ads by Google